Communicational Leadership in Higher Education: Examining Its Predictive Role in Teaching Performance from Students’ Perspectives - Mamani, Emilio Flores; et al. (European Journal of Social Science Education and Research, 2026)
This study examined the predictive influence of communicational leadership on university teaching performance from the perspective of students. A quantitative approach was adopted through a correlational-predictive research design, involving a sample of 330 students from the National University of the Altiplano during the 2025 academic period. Linear regression analyses revealed that communicational leadership constitutes a statistically significant predictor of teaching performance, accounting for 41.2% of its variance (R² = 0.412, p < 0.001). Regarding its dimensions, pedagogical communication demonstrated a strong association with planning competence (R = 0.798), whereas motivational communication emerged as the most influential predictor across the dimensions of teaching practice, assessment, and classroom interaction. These findings highlight the pivotal role of communicational leadership in fostering effective teaching performance, suggesting that communicative clarity, motivational capacity, and pedagogical enthusiasm positively shape students’ perceptions and contribute to more comprehensive and effective instructional practices in higher education contexts.